Adopting Mobile Application for Missing Person Finder: A Case Study of “U-NAI” Application - mornmoung, rachadaporn (Journal of Digital Communications, 2022)
When a family member went missing, especially a child, the chances of them returning home safely were much lower if it has been a long time. The first 72 hours of being lost were critical in many countries. Tracking down a missing person as soon as possible increased chances of survival and reuniting with families. This article aims to study the use of mobile application to track missing persons in foreign countries, and to develop the “U-NAI” application on mobile devices to track missing person in Thailand. Documents and researches from abroad and in Thailand were studied as guidelines for developing the application. The study result found that families of missing person could find information about him or her through the application in a timely manner, and could report the missing case by themselves. Photos and information of the missing person could also be shared on other social media platforms. However, to successfully track the missing person, a complete database system must be available, and for ultimate benefits, the civil society should be encouraged to use the application.